Case report: Dendritic cell-cytokine induced killer cell therapy in subjects with chronic lymphocytic leukemia and peritoneal cancer - Mehling, Brian; Wu, DongCheng; O’Gorman, Ellen; Sheridan, Daniel; Santora, Doreen; Mihályová, Renata (Frontiers in Medicine, 2023)
This study aimed to characterize the safety and efficacy of DC-CIK therapy in two patients with previously treated chronic lymphocytic leukemia or peritoneal cancer, respectively. Participants had received conventional chemotherapy treatment for their specific cancers, and in addition, 1-2 treatments of DC-CIK therapy were administered to subjects over the course of one year. Subject A received an initial dosage of 3 intravenous infusions of DC-CIK therapy on three successive days and a repeat dosage 6 months later. Subject B received an initial dosage of 3 intravenous infusions of DC-CIK therapy on three successive days and received further chemotherapy after approximately one year.No treatment-related adverse events were reported, and both patients experienced favorable outcomes from the treatment, including enhanced treatment response, increased chemotherapy tolerance, and prolonged survival in comparison to typical 5-year survival rates.